HIV heterosexual transmission to stable sexual partners of HIV-infected Brazilian hemophiliacs - Nicolau, José Eduardo; Benard, Gil; Fonseca, Luis Augusto Marcondes; Casseb, Jorge Simão Rosário; Sato, Maria Natomi; Cianga, Marcia; Tanji, Mauri Massani; Lorenzi, Therezinha Ferreira; Duarte, Alberto José da Silva (São Paulo Medical Journal, 1996)
Nineteen Brazilian HIV-infected hemophiliacs and their stable heterosexual sexual partners were studied with the aim of assessing the rate of HIV transmission in this at risk group. The mean length of relationship between couples was 7.4 years. The hemophiliac men were Class II (n=6), III (n=11) and IVa (n=2) of the CDC classification. They had decreased CD4+ and elevated CD8+ cell numbers; five had p24 antigenemia. We found 3 HIV-infected women (15.8 percent) by routine and confirmatory tests, a prevalence similar to that seen in other countries. They were asymptomatic and had no detectable p24 antigenemia. The 3 seropositive women's partners were Class II and III-CDC, and had normal CD4+ and CD8+ values and no p24 antigenemia. All seronegative women also had normal CD4+ and CD8+ numbers, except for elevated CD8+ cells in three of them, but immune abnormalities had already been seen in some seronegative partners at high risk for HIV infection. Our results reinforce previous suggestions that heterosexual transmission to stable female partners occurs preferentially early after initiation of sexual exposure, and possibly when the transmitter has high levels of viremia and regular sexual activity.